Evaluation of influence of multyfunctional additives on operational and technical parameters of petrol - Роїк, Ірина Володимирівна; Василькевич, Олександр Іванович; Бондаренко, Сергій Григорович; Степанов, Микола Борисович (Eastern-European Journal of Enterprise Technologies, 2013)
The article grounds the usefulness of multifunctional additives for petrol in order to improve the environmental characteristics of the performance of internal combustion engines. On the basis of surfactants and antioxidants a number of additives was developed. Choosing antioxidants was based on determination of their thermal stability. The influence of additives on the octane number of petrol and the process of cool-flaming oxidation of hydrocarbon fuel was studied. For the research a high-precision octanometer was used, where the octane number of petrol is determined solely by the nature and magnitude of the thermal effects associated with the occurrence of only cool-flaming oxidation reactions. Test results show that additives influence the nature of the oxidation processes. The greatest positive effect of the antioxidant 4,4 '-dioctyldiphenylamine was revealed. According to the results it was concluded that it is reasonable to use the high-temperature antioxidant 4,4 '-dioctyldiphenylamine to modify petrol.